The influences between e-service quality toward positive and opposition brand referral in Malaysia - Ayob, Nur Hidayah; Md Juperi, Nurul Zahidah; Ramli, Mohd Safwan; Mohamad Razali, Nur Hanisah; Ramdzan Ali, Al Amirul Eimer (Human Resource Management Academic Research Society, 2023)
Telecommunication sector is one of the drivers in the new digitalization era by providing the basis for business expansion and flow of investment through the communication. In Malaysia, this sector had faced some of the challenge regarding the customer perception which led the industry facing some negative brand referral and directed the brand evangelism failed to develop. Therefore, this research aims to identify the influences between e-service quality dimension consist of responsiveness, ease of use, privacy & security, functionality, reliability, efficiency towards the positive brand referrals as well as oppositional brand referrals. Through quantitative analysis, questionnaires were distributed, and the answers were analyzed. Based on the analysis conducted, it was found that reliability, functionality, and ease of use significantly contributed in predicting the positive brand referral. While reliability, privacy, and functionality significantly supported in predicting the oppositional brand referral in Malaysia